Main functional elements having defects of illegal residential buildings: The case of Cova da Moura District. - Vilhena, A. (2012)
The purpose of the paper is to describe the main functional elements with defects in illegal residential buildings. Three research questions are addressed: What are the main functional elements with defects in buildings and in dwellings? What are the main defects found? In which way these defects affect the use of buildings? The defects were identified during a survey to the building stock of the Cova da Moura District (Amadora, Portugal), carried out in 2008. This district is made of illegal constructions, occupies an area of 16.5 ha and has approximately 5,000 inhabitants. During the survey 833 buildings and 1884 units were inspected. The main results are: a) only 13% of these building presented defects in the building structure; b) about 60% of the buildings have defects in the roofing systems (e.g., damp and mould, infiltrations); c) more than 84% of the dwellings have defects in the technical installation such as gas or electrical installations most of them classified as severe defects. The main conclusion is that most of the defects detected configure serious risk scenarios, particularly in terms of the minimum habitability conditions and fire safety. However, defects related to structural stability were not as serious as expected for this kind of construction.